Background of the Sociedad Neurológica Argentina: Current state and concerns about neurologic education - Correale, Jorge (2013)
Neurology in Argentina emerged toward the end of the 19th century, following the origin of the specialty in Europe. Its development can be divided into 3 periods. The first is the specialty of neurology as part of internal medicine. Doctoral theses and publication about neurologic topics are found early in the history of medicine, but merged into internal medicine. The second period is the foundation of clinical neurology under the typical European influence, mainly French, when the first neurologists appear. This period started in 1885 with the creation of the Hospital San Roque de Buenos Aires' first nervous diseases department. Its first chair was José María Ramos Mejía, MD. In 1887, 5 years after Jean-Martin Charcot was awarded the chair of neurology at the Salpêtrière in Paris, Ramos Mejía became the first professor of neurology in South America, at the University of Buenos Aires. The third period is the emergence of subspecialty practices. During the 1970s—reflecting the North American influence—there was a new paradigm favoring the division of different disciplines. Specialists in epilepsy, stroke, headache, dementia, and multiple sclerosis, among others, began to emerge.